Keragaman Kondisi Salinitas Pada Lingkungan Tempat Tumbuh Mangrove di Teluk Kupang, NTT - jeriels matatula (School of Postgraduate Studies, Diponegoro Univer, 2019)
Mangrove forest ecosystems are habitat of various types of microorganisms, but now, problems of mangrove forests experience are in quality and wealth. Efforts to rehabilitate activities mangrove forests againts had been carried out but the results shown had not been maximized, so it is need the correct strategies to achieve the success for rehabilitation activities. The studied was conducted in Teluk Kupang, East Nusa Tenggara, covered coastal areas of Kupang's mangrove forests and coastal mangrove forests in Kupang district. The method used in this studied was a systematic sampling method that was systematically distributed across all the mangrove forest areas. The method used for salinity measurement was method of transmission and Transect Line Plots. Measurements was made in straight line and the size of the plot is 10 m x 10 m, the distanced between lines was 50 meters so that total lane is 547 with the number of plots of observation 1641 plots. The value of measurement results was made into the spread of salinity used the interpolation method. The condition of the crossed of mangrove forest located on coastal panoramas of Kupang city shows a salinity value of 10,26 - 26.33%, while salinity conditions was on the coast of Kupang ten district 10-42.33 ‰. The salinity condition was formulation of the environmental conditions mangrove forest on coast of the island as well as attempts to support management of mangrove forest activities. The distribution of different mangrove forest conditions along the coastal zone of North Sumatra shows an environmental condition that supports mangrove growth even though in some places the salinity values are high. Results of this study of salinity conditions is a study of the environment of mangrove growth so that it can provide an overview for the government in conducting various activities to rehabilitate mangrove forests.